Community empowerment model for hypertension control through integrated health post services for the elderly - Yoroh, Meilan Sondakh Apena; Maino, Irny E; Rahman, Asep (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is a major public health problem among the elderly, requiring community-based promotive and preventive approaches. The Elderly Integrated Health Post serves as a community empowerment strategy for hypertension control at the village level. Purpose: To analyze the implementation of community empowerment in hypertension management through the Elderly activities. Method: A descriptive qualitative approach was employed. In-depth interviews were conducted with eight informants consisting of health workers, the elderly integrated health post, village officials, and elderly participants as program beneficiaries. Data were analyzed thematically to identify implementation processes as well as supporting and inhibiting factors. Results: The findings indicate that community empowerment has been implemented through cadre involvement in blood pressure screening, health education, and monitoring of elderly health status. The Elderly the elderly integrated health post serves activities cover promotive and preventive aspects, including healthy lifestyle education and early detection of hypertension. Cross-sector collaboration between the primary health center and the village government supported program implementation. However, limited elderly participation, inadequate cadre training, and the reduction of supporting activities such as elderly exercise programs due to the elderly integrated health post serves integration have hindered optimal implementation. Conclusion: Community empowerment in hypertension management through the Elderly has been implemented but has not yet achieved optimal outcomes. Strengthening cadre capacity, providing continuous training, and developing more persuasive communication strategies are essential to enhance elderly participation and ensure program sustainability. Keywords: Community Empowerment; Elderly the Elderly Integrated Health Post Serves; Hypertension; Health Promotion; Primary Health Care.